Comparison of Two Types of Instruction in Physical Education - Nur, Lutfi; Malik, Arief Abdul; Juditya, Silvy; Kastrena, Ervan; Widyawan, Dena; Agustan, Boby; Budi, Didik Rilastiyo; Ardha, Muchamad Arif Al; Yang, Chung Bing (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to know the effectiveness of physical education learning models using polar global positioning system (GPS) tool. This study evolved 57 students of class VII (12-13 years old) of Junior High School Lab School UPI Bandung. The researchers used quasi-experimental research using counterbalanced design. The instruments were Polar GPS RC3 and Polar Heart Rate Sensor H3 to measure the students’ heart rate and distance during the learning process. The study showed that the average acquisition of the students’ heart rate and distance during the learning process with the tactical learning model was higher than the technical learning model. It can be concluded that tactical learning model is more effective than technical learning model to be applied to the sport games learning if reviewed from the aspects of the students’ heart rate as well as the distance.